Logic Programming for Orthogonal Graph Drawing on Restricted Grids - Strąk, Łukasz; Wieczorek, Wojciech; Nowakowski, Arkadiusz (Procedia computer science, 2025)
This paper investigates the use of logic programming—specifically, Answer Set Programming (ASP)—as a declarative approach to orthogonal graph drawing on restricted grids. The drawing problem is encoded as a constraint satisfaction problem that enforces planarity, orthogonality, and spatial constraints within bounded integer grids. Experimental results on benchmark graphs indicate that the approach generates valid and aesthetically pleasing layouts, particularly for small and medium-sized instances. These findings demonstrate the promise of declarative programming in supporting constraint-driven graph layout methodologies.